Presence of the fungus-growing ant Mycetophylax morschi (Hymenoptera, Formicidae) in a valuable area of pampas grassland in a mountainous area in the southeast of Buenos Aires province, Argentina - Arcusa, Juan Manuel (2022)
The genus Mycetophylax belongs to the subfamily Myrmicinae, tribe Attini, and is one of the lesser-known genera of fungus-growing ants. Of the three Mycetophylax species, only M. morschi was cited for Argentina. This species is also well represented in various coastal locations with sandy beaches in eastern Brazil. The present work represents the second record of the species for the Province of Buenos Aires and for Argentina and the first collection record of this species in a grassland placed in a mountainous environment.